Compared Between Ipv6 And With Ipv4,Differences And Similarities - AbouSalem, Z. Z.; Ashabrawy, M. A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2018)
This paperprovides Advantages of using IPv6 andcomparison of IPv4 and IPv6,For that, it’s critical to understand the differences and similarities, Some points in the near future when the sheer size of billions new devices will throw the IPv6 switch.IPv4 and IPv6, where IPv6 is the enhanced version of IPv4, There are various differences between IPv4 and IPv6 protocol including its features, but the critical one is the number of addresses (Address space) it creates. In my paper, I will explained the main Advantages (differences between both protocols)of IPv6 & IPv4, By giving results that can be obtained through the diffusion of technology.